2005
DOI: 10.1002/jssc.200400084
|View full text |Cite
|
Sign up to set email alerts
|

The determination of sulfonamides in honey by high performance liquid chromatography – mass spectrometry method (LC/MS)

Abstract: The sulfonamides (SAs) are stable chemotherapeutics used against the bacterial disease affecting bees, known as American foulbrood (Bacillus larvae), so their residues could appear in the honey of treated bees. Their presence at a concentration above the limit value could be a potential danger to human health. Therefore, a simple, rapid, and reliable method for determination of 11 available SAs in honey was optimized. The samples were homogenized and cleaned with extraction on solid phase by means of Chromabon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…CAP ionizes well in the negative mode with the parent m/z ) 321 producing daughters of m/z ) 257 and 152 under the proper conditions. An alternative or additional choice of fragments can include Historically, sulfonamides have been analyzed in positive mode in a variety of applications (36)(37)(38)(39)(40)(41). However, these compounds have also been found to ionize well with ESI negative.…”
Section: Resultsmentioning
confidence: 99%
“…CAP ionizes well in the negative mode with the parent m/z ) 321 producing daughters of m/z ) 257 and 152 under the proper conditions. An alternative or additional choice of fragments can include Historically, sulfonamides have been analyzed in positive mode in a variety of applications (36)(37)(38)(39)(40)(41). However, these compounds have also been found to ionize well with ESI negative.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to realize that the CEC system operates with small sample quantities (nanolitre amounts) and sample vials used for the introduction of the sample only require microlitre quantities (typically greater than or equal to 50 µl), which is quite attractive for precious biological samples [7]. Several CEC studies on SA separations have been also reported by Wang & Ye [8] and Krivohlavek et al [9]. In these cases, C18 packed columns were used to analyse SAs; however, long separation time or poor peak resolution was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods using CE with UV , fluorescence , electrochemical (ED) , and MS detection have been used for the determination of these drugs in meat, tissues, tablets, and human urine samples, respectively. But the most commonly used methods include LC using UV diode array , fluorescence , MS , or MS/MS detection . These methods require significant amounts of time associated with clean‐up steps, sophisticated instrumentation, and skilled operators.…”
Section: Introductionmentioning
confidence: 99%